Lymphoma and the Kidney: A Kidney Biopsy Teaching Case - Vincenzo L’Imperio (Kidney Medicine, 2020)
Lymphomatous infiltration of kidney parenchyma is a frequent complication of systemic hematologic malignancies and often shows subtle clinical presentation. Diffuse large B-cell lymphoma represents the most frequent form involving the kidney, with advanced stage at diagnosis, poor outcome, and risk for central nervous system relapse if not adequately treated. Kidney biopsy can provide specific and early detection of these cases, helping in the differential diagnosis with more frequent entities. Finally, further hematologic workup (bone marrow biopsy, complete blood cell count, and positron emission tomography) can distinguish secondary involvement of the kidney from the rarer kidney-limited forms, especially in patients without a previous diagnosis of lymphoma. Making a prompt and correct diagnosis directs the management of these cases and may improve the outcome, as described in the present report.